"It takes time to build trust": a survey Ontario's school-based HPV immunization program ten years post-implementation - Eve Dubé; Sarah Wilson; Dominique Gagnon; Shelley L. Deeks; Vinita Dubey (Taylor & Francis Group, 2021)
Objectives Describe Ontario's school-based human papillomavirus (HPV) vaccination program from the perspective of local public health units (PHUs). Methods In 2018, Vaccine Preventable Diseases (VPD) managers at each of Ontario's 35 PHUs were invited to participate in an online survey regarding the organization and delivery of their HPV vaccination program. Questions were asked on the school-based program, training and support of vaccine providers, communication and promotion, assessing coverage rates and perceptions of the program's strengths and challenges. Descriptive statistics were generated for close-ended items. A thematic content analysis was performed for open-ended items. Results Eighteen PHUs (54%, n = 19/35) responded. All responding PHUs provided the HPV vaccine in publicly funded schools but only 6 reported being permitted to provide HPV vaccine in private schools. Fact sheets, Q&As or other written information locally developed by the PHUs were the main tools used to communicate with parents (n = 17), students (n = 13), school personnel (n = 13) and school board officials (n = 9). The most frequently reported barriers were: limited program resources, negative perceptions held by parents and/or school staff regarding the HPV vaccine, logistical issues (e.g., getting the consents forms returned, collaboration with schools for vaccine delivery) and the fact that HPV vaccination is not mandatory under Ontario legislation. Conclusion Local public health units that implement HPV vaccine programs in schools identified logistical barriers, public perceptions about the HPV vaccine and the voluntary nature of the program as the main barriers.